Synthesis and application of hierarchical zeolites prepared using amino-acid mesoporogens. (February 2019) - Hong, M; Chen, Z W; Zhang, J; Dong, L; Wang, Y D; Chen, C; Qian, W; Wang, S W; Huang, Z A; Yuan, X N
Abstract: Amino-acid-templating is a newly developed versatile synthetic strategy for the effective construction of hierarchically porous architectures in zeolites. Although the role of amino acid polymerization on dealuminated zeolites has been well perceived in biochemical evolution as possible origin of life, the use of amino acids to tailor pore architectures in zeolites has merely merged. The present work provides an overview from the early studies on aluminosilicate surfaces as promoters in probiotic chemistry to our recent endeavours on designing hierarchically porous zeolites using various amino acids. The power of amino acids is depicted through assessing their multi-functional roles and the differences to that of surfactant templates. The key advantages using amino acids as mesoporogens include wide availability and rich diversity offering cost efficiency and unparalleled control of zeolite architecture, minimal interference on the 3D continuous zeolite crystallization, easy removal through washing with water, and amino acid recyclability. Finally, the application of amino-acid-mediated hierarchical zeolites and potential industrial usage are highlighted.